A virtual clinic for diabetes self-management: pilot study. - Jennings, A; Powell, J; Armstrong, N; Sturt, J; Dale, J (2009)
BACKGROUND: Internet-based interventions to assist in diabetes management have the potential to provide patients with the information and support they need to become effective self-managers. OBJECTIVE: To assess the feasibility, acceptability, and effectiveness of an Internet-based virtual clinic designed to facilitate self-management in patients who used insulin pumps to manage their diabetes. METHODS: For a period of 6 months, 17 patients joined the virtual clinic. The system allowed patients to communicate with health professionals, interact with peers and access information. HbA1c, quality of life, and self-efficacy were monitored at baseline and after 6 months. Questionnaires and qualitative interviews examined patient experiences. RESULTS: Participants found the virtual clinic easy to use and positively rated its design. Peer support was the most valued aspect and the discussion boards the most used component. All participants highly rated the virtual clinic in terms of improving communication with peers, but few agreed it had improved communication with health care professionals. No significant improvements in physiological and psychological measurements were found. Regarding HbA1c measurements, there was no significant difference found between the pre- and post-test results (P = .53). Mean ADDQoL scores at baseline were -2.1 (SD 1.1, range -3.4 to -0.5) compared to -2.0 (SD 1.2, range, -4.6 to -0.4) post-test (n = 12), (P = .62). Surprisingly, patients' confidence in their ability to perform self-care tasks was found to be significantly reduced from baseline to follow up (P = .045). CONCLUSIONS: An Internet-based system to aid the management of diabetes appears feasible and well accepted by patients. The pilot study did not identify evidence of an impact on improving quality of life or self-efficacy in patients who used insulin pump therapy.